2006
DOI: 10.1295/polymj.38.57
|View full text |Cite
|
Sign up to set email alerts
|

Chain Stiffness and Excluded-Volume Effects in Polyelectrolyte Solutions: Characterization of Sodium Poly(2-acrylamido-2-methylpropanesulfonate) in Aqueous Sodium Chloride

Abstract: ABSTRACT:Fourteen samples of sodium poly(2-acrylamido-2-methylpropanesulfonate) ranging in weight-average molecular weight from 1:7 Â 10 3 to 1:4 Â 10 6 have been studied by static light scattering (or sedimentation equilibrium) and viscometry to characterize the polyelectrolyte in 0.05 and 0.5 M aqueous NaCl at 25 C. The measured intrinsic viscosities (except for the two lowest molecular weights) and radii of gyration in the respective solvents are consistently described by combinations of the theories for un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(48 citation statements)
references
References 29 publications
2
46
0
Order By: Relevance
“…The value of k¢ H for typical flexible polymers in a good solvent was reported over a range from 4 to 6. 38 The value of k¢ H calculated from the literature data 39 Figure 3 shows the C s dependence of k¢ H for free PMAPS (J) and PMPC (&) in aqueous NaCl solutions at 25 1C, together with that of free poly(styrene sulfonate sodium salt) (NaPSS; M w ¼2.56Â10 5 g mol À1 ) 41 (D) and poly(2-acrylamido-2-methylpropanesulfonate sodium salt) (NaPAMPS; M w ¼2.76Â10 5 g mol À1 ) 42,43 (B) with the same molecular weight. The values of k¢ H for PMAPS and PMPC in aqueous NaCl solutions were revealed to be 1.5-8, which may be regarded as a y-state and a good solvent state, indicating the reduction in intramolecular and intermolecular interaction between polymer chains with increasing C s .…”
Section: Resultsmentioning
confidence: 96%
“…The value of k¢ H for typical flexible polymers in a good solvent was reported over a range from 4 to 6. 38 The value of k¢ H calculated from the literature data 39 Figure 3 shows the C s dependence of k¢ H for free PMAPS (J) and PMPC (&) in aqueous NaCl solutions at 25 1C, together with that of free poly(styrene sulfonate sodium salt) (NaPSS; M w ¼2.56Â10 5 g mol À1 ) 41 (D) and poly(2-acrylamido-2-methylpropanesulfonate sodium salt) (NaPAMPS; M w ¼2.76Â10 5 g mol À1 ) 42,43 (B) with the same molecular weight. The values of k¢ H for PMAPS and PMPC in aqueous NaCl solutions were revealed to be 1.5-8, which may be regarded as a y-state and a good solvent state, indicating the reduction in intramolecular and intermolecular interaction between polymer chains with increasing C s .…”
Section: Resultsmentioning
confidence: 96%
“…Aqueous 0.05 M NaCl was used as "salt buffer" for complex formation in this work, such concentration is sufficient to eliminate large change in ionic strength of solution during the addition of the initiator. Also such concentration is sufficient to overcome the polyelectrolyte effects for PAMPS-Na macromolecules [34].…”
Section: Synthesis Of Monomersmentioning
confidence: 99%
“…The authors of [34] analyzed the dependence between the radii of gyration of PAMPS-Na macromolecules and their molecular masses and, taking into account the long-range intrachain interactions, determined the values of persistent length a p = 3 nm in 0.05 M NaCl solutions. Using the simple relationship a p = A ∕ 2, we can calculate the Kuhn segment length (A = 6 nm).…”
Section: Molecular Characteristics Of Initial Components Of Pecs and mentioning
confidence: 99%
“…In previous work, 6,7 we estimated q and B (the excluded-volume strength) for sodium poly(2-acrylamido-2-methylpropanesulfonate) (Na PAMPS), an intrinsically flexible polyelectrolyte, in 0.05 and 0.5 M aqueous NaCl from data for the intrinsic viscosity [], the mean-square radius of gyration, and the translational diffusion coefficient with the aid of the quasitwo-parameter (QTP) theory [8][9][10] for the wormlike chain or, more generally, the helical wormlike chain. 10 We found that this theoretical scheme for nonionic chains is capable of consistently describing excluded-volume effects on the three properties of the polymer in the aqueous salts.…”
mentioning
confidence: 94%
“…In the work reported below, these parameters for Na PAMPS are estimated as functions of C s in the range from 0.005 to 1 M and compared with predictions from polyeletrolyte theories. [2][3][4][5]18 EXPERIMENTAL Samples PAMPS samples 6 previously synthesized and stored in the Na salt form were subjected to repeated fractional precipitation with 0.1 M aqueous sodium acetate as the solvent and acetone as the precipitant in the manner described in ref 6. From a number of fractions obtained, nine appropriate middle ones, designated below as F-H1, F-H2, .…”
mentioning
confidence: 99%